Filmes periféricos e as margens do cinema brasileiro : um estudo de caso a partir do longa-metragem Cartão Postal - Santos, Yasmin Bidim Pereira dos (Universidade Federal de São Carlos, 2015)
This work focuses on Brazilian independent cinema and the new paths cinematographers, specially the young ones, are following to make movies. The idea is to observe the new contemporary Brazilian cinema scene and some of its own characteristics, highlighting non traditional subsidezed funds, exhibition and distribution options on alternative channels, such as the internet, film clubs and festivals, as well as aesthetic aspects of its production. Their movies can be understood as peripheric as they may be found outside the scope that includes instutionalized cinema. So 'Cartão Postal' (Josinaldo Medeiros and Wagner Novais, 2011) will be our study case, since it is a movie that can be called peripheric and it is also fit in a specific genre of movie that has been produced on favelas, called cinema de periferia. This movie will be studied on its formal aesthetic dimension as well as on its production strategies, observing how it can fit into some of the main characteristics of this new Brazilian scene.
Keywords: Cinema periférico; Cinema brasileiro contemporâneo; Filmes de periferia; Peripheric cinema; Contemporary brazilian cinema; LINGUISTICA, LETRAS E ARTES